2019
DOI: 10.14710/jitaa.44.2.125-134
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the SNP g. 1180 C>T in leptin gene and its association with growth traits and linear body measurement in Kebumen Ongole Grade cattle

Abstract: ABSTRAKPenelitian ini bertujuan mengetahui polimorfisme gen leptin sapi PO Kebumen dan asosiasinya dengan sifat pertumbuhan. Seratus sampel darah sapi dikoleksi untuk analisis molekuler. Polimorfisme gen leptin dianalisis menggunakan 2 teknik: Polymerase Chain Reaction -Restriction Fragment Length Polymorphism (PCR-RFLP) menggunakan enzim restriksi HpyCH4V dan sekuensing. Asosiasi antara gen leptin dan sifat pertumbuhan dianalisis menggunakan T-test. Hasil penelitian menunjukkan ada SNP g. 1180 C>T pada gen le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…SNP g. 1180 C>Y in crossbred beef cattle was confirmed by electropherogram ( Figure 2). It has two alleles C and T. Hernández et al 2016; Orrù et al (2011);and Fathoni et al (2018) also reported that in Brahman; Simmental bulls; and Kebumen Ongole Grade cattle has SNP g. 1180 C>T (Arg/Cys). Fathoni et al (2018) reported a change in mutation g. 1180 C>T has significantly associated with high weaning chest circumference in Kebumen Ongole Grade cattle.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…SNP g. 1180 C>Y in crossbred beef cattle was confirmed by electropherogram ( Figure 2). It has two alleles C and T. Hernández et al 2016; Orrù et al (2011);and Fathoni et al (2018) also reported that in Brahman; Simmental bulls; and Kebumen Ongole Grade cattle has SNP g. 1180 C>T (Arg/Cys). Fathoni et al (2018) reported a change in mutation g. 1180 C>T has significantly associated with high weaning chest circumference in Kebumen Ongole Grade cattle.…”
Section: Discussionmentioning
confidence: 97%
“…It has two alleles C and T. Hernández et al 2016; Orrù et al (2011);and Fathoni et al (2018) also reported that in Brahman; Simmental bulls; and Kebumen Ongole Grade cattle has SNP g. 1180 C>T (Arg/Cys). Fathoni et al (2018) reported a change in mutation g. 1180 C>T has significantly associated with high weaning chest circumference in Kebumen Ongole Grade cattle. Javanmard et al (2010); Buchanan et al (2002); Konfortov et al (1999) also reported SNP g. 1180 C>T change amino acid from arginine to cysteine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…LEP hormone is encoded by the LEP gene. The bovine LEP gene is located in BTA 4q32 and consists of three exons and two introns [26]. The previous studies have associated SNP (c.73T>C) of LEP gene exon 2 with BW, fatness, and carcass quality [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have associated polymorphism with phenotypic traits, although results vary. Fathoni et al [28] had stated that the Leptin gene polymorphism g.1080C>T was associated with weaning chest circumference in Kebumen Ongole Grade cattle. Meanwhile, other researchers stated no association between genotype and meat quality, birth weight, weaning weight, daily weight gain, and body condition score.…”
Section: Leptin Gene Studies In Indonesiamentioning
confidence: 99%